Pemanfaatan Ekstrak Bunga Telang (Clitoria Ternatea L.) Sebagai Alternatif Zat Warna Lpcb Pada Pewarnaan Fungi - hamtini, Hamtini; Hakim, Syamsir; Astriani, Ranti Dwi; Fadillah, Muhammad Arief; Rahmawati, Juli (Journal of Medical Laboratory Research, 2024)
The eagle flower is a compound flower that is identical to the purple color on the petals. Vines, one of which is eagle flowers, can be found anywhere from the yard of the house to the edge of the rice field. The traditional use for this plant is as an eye medicine and food coloring, and it can also be grown as an ornamental plant. There are two types of dyes, namely dyes made from chemicals and dyes made from plants. Most of the dyes used in laboratories are generally chemicals such as KOH, methylene blue, and lactofenol, which are not good for the environment and are quite expensive. This means that it is necessary to make other dyes that are better for the environment. The purpose of this study was to determine whether or not striped leaf extract can be used as an alternative to LPCB staining in fungi. The method used in this study was maceration of telang flower extract with 96% ethanol solvent, after obtaining the extraction results then dilution was carried out with concentrations of 1%, 2.5%, 5%, 7.5% and 10% using aqueous solvents. The result of this study is that striped flower extract cannot be used as a dye in fungal coloring, this can be seen from the morphological picture of fungi that are not clearly visible and do not absorb dyes from eagle flower extract compared to LPCB dyes used as standard controls.